1991
DOI: 10.1002/cyto.990120406
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease‐induced DNA structural changes assessed by flow cytometry with the intercalating dye propidium iodide

Abstract: A flow cytometric analysis of DNA structural changes induced by cleavage with nucleases was performed on isolated HeLa nuclei by assessing changes in stainability with the DNA-specific fluorochrome propidium iodide (PI). After mild digestion with DNAse I, micrococcal nuclease, or with the single-strandspecific S1 and Neurospora crassa nucleases, fluorescence intensity of nuclei stained with PI increased by about 15-30% above the value of undigested control samples. No significant modifications were observed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…However, the two dyes have quite different stain reactions. PI intercalates between base pairs of double-stranded DNA and RNA with little or no base specificity (Properi, Giangare, and Bottiroli, 1991), while DAPI is a nonintercalating stain that binds preferentially and in a complex manner to A-T base regions (Godelle et al, 1993). We show here that PI-based flow cytometry produces results very consistent with those based on Feulgen microspectrophotometry.…”
Section: Choice Of Fluorochromes (Pi Vs Dapi)-supporting
confidence: 67%
See 1 more Smart Citation
“…However, the two dyes have quite different stain reactions. PI intercalates between base pairs of double-stranded DNA and RNA with little or no base specificity (Properi, Giangare, and Bottiroli, 1991), while DAPI is a nonintercalating stain that binds preferentially and in a complex manner to A-T base regions (Godelle et al, 1993). We show here that PI-based flow cytometry produces results very consistent with those based on Feulgen microspectrophotometry.…”
Section: Choice Of Fluorochromes (Pi Vs Dapi)-supporting
confidence: 67%
“…PI intercalates between base pairs of double-stranded DNA and RNA with little or no base specificity (Properi, Giangare, and Bottiroli, 1991), while DAPI is a nonintercalating stain that binds preferentially and in a complex manner to A-T base regions (Godelle et al, 1993). PI is excited by visible light with an absorbancy maximum at 490 nm, while DAPI is excited by UV light at 350 nm.…”
Section: Choice Of Fluorochromes (Pi Vs Dapi)-mentioning
confidence: 99%
“…Accordingly, more recent reports (Higashikubo et al. 1990al. , Prosperi et al 1991 showed that chromatin alterations, occurring after treatment by DNAse I or micrococcal and S1 nucleases induced an increase in PI fluorescence intensity ranging between 15 and 30%.…”
Section: Discussionmentioning
confidence: 95%
“…To investigate chromatin modifications without interference by cytoplasmic components (Thornthwaite et al 1980), several nuclear isolation mediums (NIM) were used: 0.5% Nonidet-P40 (NP-40, Sigma) in Ca++-and Mg++-free PBS with or without 1 mM EDTA; 0.5% Triton-X 100 (Sigma) in Caf+-and Mg++-free PBS with or without 1 mM EDTA; 0.1% NP-40 in 0.1% sodium citrate in distilled water with or without 1 mM EDTA. A commercial NIM (Nucleidye, Ylem, Avezzano, Italy) were also used.…”
Section: Fluorescent Probes and Flow Cytometrymentioning
confidence: 99%
“…PI, being an intercalating dye, does not easily bind to tightly coiled DNA found in heterochromatin (2,13,16). Subtracting the amount of heterochromatin from each chromosome and running the correlation between euchromatin per chromosome and nuclear DNA content, however, does not improve the correlation, r = 0.63.…”
Section: Discussionmentioning
confidence: 99%